Nitrogen migration mechanism and formation of aromatics during catalytic fast pyrolysis of sewage sludge over metal-loaded HZSM-5. (15th May 2019) - Gu, Bo; Cao, Jing-Pei; Wei, Fu; Zhao, Xiao-Yan; Ren, Xue-Yu; Zhu, Chen; Guo, Zhen-Xing; Bai, Jin; Shen, Wen-Zhong; Wei, Xian-Yong
Graphical abstract: Highlights: Me-HZ greatly promoted the generation of H2, BTX and NH3 . CFP of SS over 0.5Ni-HZ presented the highest yield of aromatics. Nitrogen evolution mechanism during CFP of SS was investigated. Reaction pathway for CFP of SS over Me-HZ was proposed. Abstract: In order to effectively improve the quality of bio-oil from catalytic pyrolysis (CFP) of sewage sludge (SS) and to produce aromatic-rich bio-oil, the evolution mechanisms of nitrogen and formation of aromatics during CFP of SS over metal-loaded HZSM-5 (HZ) were investigated in depth. The results show that the presence of metals caused the slight decrease in oil-C (carbon in bio-oil) yield and the increase in gas yield and total carbon yield of aromatics. Ni-loaded HZ has a better performance than Co-loaded one in improving the carbon yield of aromatics, while the maximum yield of 11.2% was obtained over 0.5Ni-HZ. Metal-loaded HZ promoted the formation of monocyclic aromatics rather than polycyclic aromatics and Ni significantly enhanced the selectivity of benzene. With the addition of Ni and Co, more nitrogen was released as NH3 or fixed in solids. NH3 yield increased by raising the metal loading, and the highest NH3 yield of 36.8% was obtained over 3.0Ni-HZ. Ni and Co promoted the cracking reactions during CFP to generate more H radicals, which have advantages to the ring-opening of N -containing heterocycles in SS to produce aromatics and NH3 . A possible catalytic mechanism of CFP of SS over metal loaded HZ was proposed in this study.